Effect of multiple intra-articular injections of polynucleotides on treatment of intractable knee osteoarthritis: A case report. Issue 49 (December 2017) - Mun, Jong-Uk; Cho, Hyung Rae; Choi, Young Soon; Kim, Young Uk
Abstract: Rationale: Knee osteoarthritis (KOA) is a chronic joint degenerative disease. Intra-articular injection (IAI) of hyaluronic acid (HA) is widely used to treat KOA. However, some HA injections have no effect at all. Polynucleotides (PN) are recently noted as a valid substitute for HA. Patient concerns: A 61-year-old female was admitted to the pain center with symptoms of pain over the knee and warmth feeling with stiffness in the left knee. The patient reported chronic severe pain in the left knee area despite 6 times IAI of HA. She had past medical history of breast cancer and thyroid cancer. Diagnoses: She was diagnosed as having KOA. Interventions: Ultrasound-guided IAI of PN was carried out 3 times in 3 weeks. Outcomes: She was followed-up for more than 5 months with good improvement in intractable knee pain without any adverse event. Lessons: IAI of PN is an efficient therapeutic option for KOA treatment if HA injection is unsuccessful.